The Explanation Of E-Service Quality and Actual Use of M-Banking - Az-Zahra, Shafira; Setiawati, Lina; Sosianika, Adila; Senalasari, Widi (Politeknik Negeri Bandung, 2023)
Technological developments are increasingly rapid from time to time, causing all areas of the business sector to be required to be adaptive. One of which is the banking sector. The digital era has made mobile banking an option to facilitate transaction activities. The actual use of mobile banking is a real-world interpretation to explain the impact of electronic service quality more comprehensively. This study aims to explore mobile banking users in Indonesia. The quality of e-service in mobile banking uses the Technology Acceptance Model (TAM) approach. The survey was conducted in Bandung with 202 mobile banking users; the data were analyzed using SMART PLS with the methods of reliability test, validity test, hypothesis test, and mediation analysis to be able to interpret the research objectives more specifically. The findings indicate e-service quality significantly impacts attitudes towards m-banking, perceived usefulness, and perceived ease of use. It points out that internet-based transactions, especially mobile banking systems, should be made easier, safer, and more convenient for consumers to use.